Republic of Tajikistan : Report on the Observance of Standards and Codes (ROSC)-Data Module. (IMF Staff Country Reports; Country Report, 2005)
This Report of the Observance of Standards and Codes (ROSC) Data Module provides an assessment of Tajikistan's macroeconomic statistics against the recommendations of the General Data Dissemination System (GDDS), complemented by an assessment of data quality based on the IMF's Data Quality Assessment Framework. The assessment reveals that Tajikistan already meets many of the GDDS recommendations for dissemination of macroeconomic statistics. The main exceptions are the coverage of national accounts, central government operations, and central government debt. All data categories meet or exceed the recommended periodicity and timeliness.